2016
DOI: 10.3390/ijms17091441
|View full text |Cite
|
Sign up to set email alerts
|

Property Characterization and Photocatalytic Activity Evaluation of BiGdO3 Nanoparticles under Visible Light Irradiation

Abstract: BiGdO3 nanoparticles were prepared by a solid-state reaction method and applied in photocatalytic degradation of dyes in this study. BiGdO3 was characterized by X-ray powder diffraction, X-ray photoelectron spectroscopy, scanning electron microscopy, Brunauer-Emmett-Teller, UV-Vis diffuse reflectance spectroscopy and transmission electron microscopy. The results showed that BiGdO3 crystallized well with the fluorite-type structure, a face-centered cubic crystal system and a space group Fm3m 225. The lattice pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 111 publications
(101 reference statements)
1
5
0
Order By: Relevance
“…X-ray powder diffraction patterns of the BiGdO 3 nanoparticle are shown in figure 2(A). The results are the same as simulation and experimental x-ray powder diffraction patterns of BiGdO 3 nanoparticles which are reported by Luan et al (2016). Coating PEG on BiGdO 3 nanoparticles was proved by FT-IR spectra.…”
Section: Characterization Of Synthesized Nanoparticlessupporting
confidence: 85%
See 1 more Smart Citation
“…X-ray powder diffraction patterns of the BiGdO 3 nanoparticle are shown in figure 2(A). The results are the same as simulation and experimental x-ray powder diffraction patterns of BiGdO 3 nanoparticles which are reported by Luan et al (2016). Coating PEG on BiGdO 3 nanoparticles was proved by FT-IR spectra.…”
Section: Characterization Of Synthesized Nanoparticlessupporting
confidence: 85%
“…In this study, for the first time, BiGdO 3 nanoparticle was prepared by the sol-gel conventional method. However, so far only one paper has been published by Luan et al (2016) in which the BiGdO 3 nanoparticles were synthesized by a different method (by a solid-state reaction method) for photocatalytic activity. The advantage of our method (sol-gel) over the previous work's method is the synthesizing of the nanoparticles with a more simple and inexpensive method.…”
Section: Discussionmentioning
confidence: 99%
“…Semiconductor based technology which utilizes solar energy for the mineralization of textile pollutants has been considered as a green and viable strategy [2]. Many visible light sensitive photocatalysts such as BiVO 4 , Bi 2 O 3 Bi 2 WO 6 , WO 3 and Fe 3 O 4 have been employed for the abatement of organic pollutants [3,4]. But, magnetite with formula MFe 2 O 4 , where M represents the metallic cations like Fe, Co, Ni, Cu, Mg and Mn, has attracted a great deal of attention in the remediation of organic pollutants [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Nasser et al [ 33 ] reported that the energy change caused by Sb doping obviously led to the decrease of the band gap energy of ZnO. Moreover, previous works have shown that the photo-excitation of electrons in an O2p and Bi6s hybrid orbital may result in a charge transfer occurring to a d orbital of the other metal in the composite oxide [ 34 , 35 , 36 ]. Sn-Sb-Bi composite oxides may respond to visible light irradiation because Sn and Sb respectively occupy 5d orbits in the ground state.…”
Section: Introductionmentioning
confidence: 99%